Developing Students’ Multicultural Background in Structure Courses (International Journal of Active Learning, 2019)
In applying English sentence structure, learners need to know the patterns that must be mastered. In addition, in making sentences learners need to pay attention to different cultures between one learner and another. This study discusses the background of students’ various cultures. This diversity is in terms of regional origin or provinces, mastered languages, and hobbies. However, this study focuses on hobbies. Student hobbies include: reading books, reading novels / comics, writing novels, graphic design, drawing, and so on. This is what encourages researchers to know the benefits of hobbies in learning English sentence structure. In this study researchers propose the problem